Job satisfaction of nurses with master of nursing degrees in Poland: quantitative and qualitative analysis - Aneta Brayer; Ludmila Marcinowicz (BMC, 2018)
Abstract Background Understanding the issue of job satisfaction of nurses with master of nursing degrees may help develop organisational changes necessary for better functioning of health care institutions. This study aimed to evaluate the level of job satisfaction among holders of Masters of Nursing degrees employed at health care institutions and to ascertain its determinants. Methods The cross-sectional study was carried out in randomly selected health care institutions in Poland using the Misener Nurse Practitioner Job Satisfaction Survey and an original survey questionnaire with two open-ended questions. Quantitative data were analysed using descriptive and summary statistics. Results The participants gave highest satisfaction ratings to their relationships with direct superiors and other nurses, as well as their social contacts at work. The lowest ratings were given to the pension scheme and factors connected with remuneration. A highly statistically significant relationship was found between the job classification and the level of professional satisfaction (p < 0.001). Qualitative analysis of responses to the two open-ended questions supported Herzberg's Two-Factor theory: internal factors promoted satisfaction, whilst external ones caused dissatisfaction. Conclusions Managers of nurses should strengthen the areas that contribute to higher employee satisfaction, particularly interpersonal relationships, by commendation and recognition of work effects.